Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1093/ajcp/107.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the Mucosa in Sigmoid Colon Specimens With Diverticular Disease:Observations for the Interpretation of Sigmoid Colonoscopic Biopsy Specimens

Abstract: We examined retrospectively 100 sigmoid colon resection specimens removed for diverticulitis (DD [diverticular diseasel-diverticulitis), 53 adenocarcinoma specimens that also had diverticulosis (DD-adenocarcinoma), and 50 adenocarcinoma specimens that did not have DD (adenocarcinoma only) to study the mucosal changes that occur in DD. Documenting these histologic features could be helpful in deciphering changes seen in colonoscopic biopsy specimens from the sigmoid colon in older patients. Prominent mucosal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 16 publications
0
13
1
4
Order By: Relevance
“…However, the study reported that there was no correlation with the type or duration of symptoms, endoscopic evidence of mucosal inflammation, or length of colon resected. Despite lack of correlation between symptoms and inflammation, this retrospective work highlights the possible relevance of clinically undetected low-grade colitis 60 or pericolic abscess formation in patients who are chronically symptomatic.…”
Section: Inflammatory Changesmentioning
confidence: 91%
“…However, the study reported that there was no correlation with the type or duration of symptoms, endoscopic evidence of mucosal inflammation, or length of colon resected. Despite lack of correlation between symptoms and inflammation, this retrospective work highlights the possible relevance of clinically undetected low-grade colitis 60 or pericolic abscess formation in patients who are chronically symptomatic.…”
Section: Inflammatory Changesmentioning
confidence: 91%
“…The initial inflammatory histopathologic features of diverticulitis are prominent mucosal folds with mild cryptitis, crypt distortion, mucosal ulcerations, and periostal inflammatory infiltrates composed of lymphocytes, neutrophils, and activated macrophages [ 11 , 12 , 13 ] (fig. 1b ).…”
Section: Pathomorphologic Events Leading From Diverticulosis To Divermentioning
confidence: 99%
“…Zusätzlich kann ein verengter Divertikelhals zur längeren Retention von keimbelasteten Stuhl im Divertikellumen sowie zur Bildung von Kotsteinen führen, die über eine mechanische Irritation des Divertikelrands Druckulzerationen hervorrufen können [20]. Histopathologisch zeigen sich prominente Schleimhautaufwerfungen mit gestörter Kryptenarchitektur und Kryptitis, Ulzerationen mit lymphozytären und neutrophilen Infiltraten, Fibrosierung der Lamina propria mucosae sowie eine Hyperplasie und Aufsplitterung der Lamina muscularis mucosae [21]. Rezidivierende Entzündungsschübe können langfristig zur lokalen Fibrosierung, Wandverdickung und Stenosierung führen, ggf.…”
Section: Prozess Der Strukturierten Konsensfindungunclassified